Beyond Words: The Translation of Emotion and Subtext in Selected Literary Texts - HANAFI, Hind (International Journal of Linguistics and Translation Studies, 2025)
Literary translation extends beyond the boundaries of words, venturing into the realm of emotion and subtext where meaning resides in the unsaid and the implied. The present study explores the translation of emotion and subtext in literary works, focusing on the intricate challenges involved in conveying implicit meanings that are not directly articulated in the source text. By analyzing Virginia Woolf's To the Lighthouse (English to Arabic) and F. Scott Fitzgerald's The Great Gatsby (English to Arabic), this research investigates how translators navigate non-verbal cues, emotional undertones, and psychological subtexts embedded in these texts. These case studies highlight the complexity of preserving emotional resonance and implicit meaning across linguistic and cultural divides. Drawing on concepts from dynamic equivalence, cultural translation, and reader-response theories, the study examines the translator's role as both a linguistic mediator and an interpreter of emotional and psychological depth. By shedding light on the strategies used to mediate emotion and subtext, this research contributes to the broader field of literary translation, emphasizing the translator's creative and interpretive role in fostering cross-cultural literary appreciation.